Pelibatan Peserta Didik melalui Metode Tajak Sare dalam Pembelajaran Daring - Jefri Soni (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2020)
The purpose of the study was to increase the participation of learners in online learning using the tajak sare method. The subject in the study was a learner of MIPA 1's XII class of 26 people. Research design uses a class action research design of as many as 2 cycles. The action that was committed was the ascetic of applying tajak sare methods. This method stands for questioning, correction (reinforcement), information sharing and reps (repetition). The method focuses on the participation of learners on indicators of noticing lessons, asking and answering, giving rebuttals/opinions, and collecting tasks on time. On each cycle consists of 2 learning encounters through video conference. In the first cycle, the learner participation level is only 37.96% classically and it increases to 64.35% in the second cycle. The magnitude of the increase between the two cycles is 26.39%. The results of this study showed that the application of sare tajak methods in online learning through video conferences could improve learner participation